Differential metabolic effects of oral butyrate treatment in lean versus metabolic syndrome subjects. Issue 5 (May 2018) - Bouter, K EC; Bakker, G J; Levin, E.; Hartstra, A V; Kootte, R S; Udayappan, S D; Katiraei, S.; Bahler, L.; Gilijamse, P. W.; Tremaroli, V.; Stahlman, M.; Holleman, F.; et al.
Abstract : Background: : Gut microbiota‐derived short‐chain fatty acids (SCFAs) have been associated with beneficial metabolic effects. However, the direct effect of oral butyrate on metabolic parameters in humans has never been studied. In this first in men pilot study, we thus treated both lean and metabolic syndrome male subjects with oral sodium butyrate and investigated the effect on metabolism. Methods: : Healthy lean males ( n = 9) and metabolic syndrome males ( n = 10) were treated with oral 4 g of sodium butyrate daily for 4 weeks. Before and after treatment, insulin sensitivity was determined by a two‐step hyperinsulinemic euglycemic clamp using [6, 6‐2 H2 ]‐glucose. Brown adipose tissue (BAT) uptake of glucose was visualized using 18 F‐FDG PET‐CT. Fecal SCFA and bile acid concentrations as well as microbiota composition were determined before and after treatment. Results: : Oral butyrate had no effect on plasma and fecal butyrate levels after treatment, but did alter other SCFAs in both plasma and feces. Moreover, only in healthy lean subjects a significant improvement was observed in both peripheral (median Rd: from 71 to 82 μmol/kg min, p < 0.05) and hepatic insulin sensitivity (EGP suppression from 75 to 82% p < 0.05). Although BAT activity was significantly higher at baseline in lean (SUVmax: 12.4 ± 1.8) compared with metabolic syndrome subjects (SUVmax: 0.3 ± 0.8, p < 0.01), no significant effect following butyrate treatment on BAT was observed in either group (SUVmax lean to 13.3 ± 2.4 versus metabolic syndrome subjects to 1.2 ± 4.1). Conclusions: : Oral butyrate treatment beneficially affects glucose metabolism in lean but not metabolic syndrome subjects, presumably due to an altered SCFA handling in insulin‐resistant subjects. Although preliminary, these first in men findings argue against oral butyrate supplementation as treatment for glucose regulation in human subjects with type 2 diabetes mellitus.